Airplug‐Mediated Isolation and Centralization of Single T Cells in Rectangular Microwells for Biosensing. Issue 1 (15th October 2019) - Sukumar, Pavithra; Deliorman, Muhammedin; Brimmo, Ayoola T.; Alnemari, Roaa; Elsori, Deena; Chen, Weiqiang; Qasaimeh, Mohammad A.
Abstract: Sorting cells in a single cell per microwell format is of great interest to basic biological studies, biotherapeutics, and biosensing including cell phenotyping. For instance, isolation of individual immune T cells in rectangular microwells has been shown to empower the multiplex cytokine profiling at the single cell level for therapeutic applications. The present study, shows that there is an existing bias in temporal cytokine sensing that originates from random "unpredicted" positions of loaded cells within the rectangular microwells. To eliminate this bias, the isolated cells need to be well‐aligned with each other and relative to the sensing elements. Hence, an approach that utilizes the in situ formation and release of airplugs to localize cells toward the center of the rectangular microwells is reported. The chip includes 2250 microwells (each 500 × 50 × 20 µm 3 ) arranged in nine rows. Results show 20% efficiency in trapping single T cells per microwells, where cells are localized within ± 3% of the center of microwells. The developed platform could provide real‐time dynamic and unbiased multiplex cytokine detection from single T cells for phenotyping and biotherapeutics studies. Abstract : Quantitative, real‐time analysis of cytokine profiles of individual immune cells is needed for precise biotherapeutic applications. The microfluidic platform isolates and centralizes a single cell per microwell in a large array of microwells by utilizing in situ generated airplugs and antibody‐coated microwell surfaces. It is demonstrated that the platform provides unbiased cytokine detection for immunophenotypic characterization of single T cells.